Respuesta :

your answer would be -624 because 1-210-3=  -212 then 3 times -212 +12= -624

Given expression : 3⋅(1-210-3)+12.

In order to evaluate the given expression, we need to apply order of operations.

According to order of operations we need to simplify parenthesis part first.

We have 1-210-3 inside parenthesis.

Therefore, 1-210-3 = -209-3 = -212.

3⋅(1-210-3)+12  => 3 ⋅(-212) +12.

Now, multiplying 3 and -212, we get -636.

3 ⋅(-212) +12 => -636 + 12

= -624.

Therefore, 3⋅(1-210-3)+12 = -624.